Mark and Paul / Pt. 2 Mark and Paul : Comparative Essays Part II For and Against Pauline Influence on Mark / edited by Eve-Marie Becker, Troels Engberg-Pedersen, Mogens Mueller - Becker, Eve-Marie; Engberg-Pedersen, Troels; Müller, Mogens (Mark and Paul, 2014)
Biographical note: Eve-Marie Becker, Aarhus University, Denmark; Troels Engberg-Pedersen andMogens Müller, University of Copenhagen, Denmark.